Social exclusion and the digital divide - Mercedes López-Aguado; Lourdes Gutiérrez-Provecho; José Quintanal Díaz; José Luis García Llamas (Je-LKS, 2022)
The recent advances in information and communication technology have given rise to radical changes in how we interact and communicate in our social, educational, and working environments. However, the potential and opportunities offered by these technologies are not fully available across society due to huge differences in their use and uptake, that is, what has traditionally been called the digital divide. Current research indicates that this divide is intimately connected to economic inequalities and social exclusion. The digital divide manifests primarily for those groups where economic resources are scarcest, and among such groups we find the lowest rates of device ownership and personal internet connection. Secondary to this, and the focus of the majority of literature on the subject, the digital divide further aggravates existing socioeconomic differences and even generates new forms of social exclusion. Taking a positive point of view, this situation does also imply that eliminating the digital divide could help alleviate social exclusion. Nevertheless, for social and educational intervention programmes to have any real effect on social exclusion, we need to have a more in-depth understanding of processes and variables that cause it at an individual level. In this way we could design interventions tailored to the personal interests, needs, limitations, and potential of every individual and that would prioritise particularly disadvantaged groups, which, according to this study include older people, the less well educated, those with health problems, and the unemployed.